2021
DOI: 10.3389/fpsyt.2021.766261
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Resilience and Extraversion on Psychological Distress and Loneliness Among the General Population of Tyrol, Austria Between the First and the Second Wave of the COVID-19 Pandemic

Abstract: Background: During the first 3 weeks of the COVID-19 pandemic, the federal state of Tyrol, Austria had one of the strictest curfews in Austria and worldwide. The aim of the current study was to investigate the assumingly protective role of resilience and extraversion and its impact on mental health following such an uncertain and unpredictable situation.Methods: Between the first and the second wave of the pandemic, adult residents of Tyrol were invited to participate in an online survey. Next to the assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 79 publications
(97 reference statements)
5
21
0
Order By: Relevance
“…In this study, resilience mediated the influence of viral anxiety on psychological well-being among all participants. In COVID-19 pandemic, people's high level of resilience was reported to related with low level of stress and high level of psychological well-being among the general population ( 54 ), even in special population such as public workers ( 55 ), schoolteachers ( 56 ), or healthcare workers ( 57 ). In this sample, however, we could not observe mediating effect of resilience among participants who were more stressful to Beirut explosion.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, resilience mediated the influence of viral anxiety on psychological well-being among all participants. In COVID-19 pandemic, people's high level of resilience was reported to related with low level of stress and high level of psychological well-being among the general population ( 54 ), even in special population such as public workers ( 55 ), schoolteachers ( 56 ), or healthcare workers ( 57 ). In this sample, however, we could not observe mediating effect of resilience among participants who were more stressful to Beirut explosion.…”
Section: Discussionmentioning
confidence: 99%
“…The control group was recruited through advertising in print media, email lists, flyer, and social media. A total of 1646 people participated in the baseline survey (findings obtained in the Tyrolean sub-sample are reported in Tutzer et al 22 and Chernova et al 36 ). They were asked to provide an email address in order to be reminded for follow-up, however, this was not a prerequisite to participate in the baseline survey.…”
Section: Methodsmentioning
confidence: 99%
“…Findings of the baseline survey are presented in Tutzer et al ( 14 ) and Chernova et al ( 15 ). Of the 961 baseline participants, 384 took part in the follow-up survey.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, study participants aged 19–49 reported to be particularly affected by loneliness and boredom ( 14 ). Importantly, the relationship between both study participants' sex and partnership situation and psychological distress and severe loneliness was mediated by resilience, and the relationship between participants' partnership situation and psychological distress was mediated by extraversion ( 15 ). In addition to investigating longitudinal changes in psychological distress, loneliness, boredom, and resilience over the course of the pandemic, the current 5-month follow-up study aimed at examining the associations between baseline resilience and extraversion on the one hand and psychological distress, loneliness, and boredom at follow-up on the other.…”
Section: Introductionmentioning
confidence: 99%